Wujud Tuturan Imperatif dalam Talkshow Vindes pada Kanal Youtube Vindes Unggahan September 2022 - Aji, Siti Khoerimah; Suroso, Eko (CV. Eduartpia Publisher, 2023)
Social life cannot be separated from communication, now the ways of communicating are increasingly diverse as technology develops. In fact, communication can be done online without having to meet each other. In communicating, often utter certain types of speech such as speech orders. In pragmatics, imperative speech is called imperative speech, meaning an utterance that is intended to order the interlocutor to do what the speaker wants. This speech certainly occurs in various kinds of communication, both directly and indirectly. A show on television, youtube, radio is also a communication. One of the talk show shows that contains imperative utterances is the Vindes talk show which is broadcast on YouTube by Vincent and Desta. This research succeeded in finding the types of imperative utterances found in the Vindes talk show uploaded September 2022. This type of research is a qualitative descriptive research. Data collection techniques using observing techniques and note-taking techniques. Based on the results of the research, the researcher found 17 forms of imperative utterances in the Vindes talk show on the Vindes YouTube channel uploaded in September 2022.Keywords: speech; imperative; order; talk show